A Scalable, Chromatography-Free Synthesis of Benzotetramisole - Daniels, David S. B.; Smith, Siobhan R.; Lebl, Tomas; Shapland, Peter; Smith, Andrew D. (Synthesis, 2015)
The scalable, chromatography-free synthesis of the chiral isothiourea benzotetramisole (BTM) in two steps from commercially available materials is presented. A detailed procedure for the synthesis of both enantiomers and the racemate on ca. 10 gram scale is disclosed.
Keywords: isothiourea; Lewis base catalysis; asymmetric catalysis; kinetic resolution; rearrangement; benzotetramisole